ASSOCIATION OF MICROSATELLITE GENETIC DIVERSITY WITH GROWTH RELATED TRAITS IN THE BASE POPULATION OF AFRICAN CATFISH, Clarias gariepinus, BREEDING PROGRAM - Imron Imron; Bambang Iswanto; Narita Syawalia Ridzwan; Rommy Suprapto; Huria Marnis (Indonesian Aquaculture Journal, 2015)
Genetic diversity at molecular level has been assumed to correlate with fitness related traits. However, accumulating evidences showed that the nature of that correlation has been variable. This study was aimed to explore the nature and possible mechanisms underlying that correlation by focusing on growth related traits in African catfish, Clarias gariepinus using microsatellite molecular markers. Fifty individual African catfish of 110 days-old were sampled and subjected to both morphological and molecular analyses. The standard length, total length and body weight as well as allelic scores of six microsatellite loci were measured on each individual. Indices of microsatellite diversity, namely individual multilocus heterozygosity (MLH) and mean microsatellite allelic distance (mean d2) for individual level, and mean observed heterozygosity (Ho) and single-locus heterozygosity (ho) for group level, were correlated to those traits using Pearson correlation coefficient (r). The Hardy Weinberg and linkage disequilibrium were carried out to explore the possible mechanisms underlying correlation. The results showed that at individual level the MLH and mean d2 were weakly correlated with standard length, (r=0.25, p<0.05) and (r=0.24, p<0.05), respectively. At group level, Ho was correlated with both standard and total length (r=0.99, p<0.05) while ho identified two loci, Cga03 and Cga06 significantly contributed to the correlation. Combining all relevant information, present study identified associative overdominance, both local effect and general effect hypotheses might responsible for the observed correlations.